APPLICATION OF BIOCHAR FOR TREATMENT OF PRODUCED WATER - MUHAMMAD HISHAM, MUHAMMAD SAID FARHAN (Universiti Teknologi PETRONAS, 2020)
Produced water is referred to as the reservoir water that is naturally produced as a byproduct during the oil and gas extraction phase and contains toxic compositions that are harmful to the environment, resulting in a compulsory treatment before disposing back to the ocean. Produced water has a complex composition, comprising of high salt concentration, emulsified oil, suspended solids, water and chemical enhancer, heavy metals and some other contaminants. Malaysia is ranked as the 18th largest tea-producer in Asia by the Food and Agricultural Organization of the United Nations, which makes TW a reliable source for biochar. TW has been discovered to have the ability to remove heavy metals in wastewater through the adsorption process, thus making it an efficient adsorbent. Chemical Oxygen Demand (COD) and Total Organic Carbon (TOC) are two of the organic contaminants comprised in the produced water system.